'The Bullock Report and European Experience': What We Can Still Learn about Worker Directors from Hugh Clegg. Issue 1 (1st September 2020) - Gold, Michael
Abstract : Hugh Clegg's paper, 'The Bullock Report and European Experience', written in 1977, analyses the role of worker directors appointed to the boards of UK companies, a move which formed part of the then Labour government's Social Contract with the trade unions designed to stem the country's long-term industrial decline. My commentary argues that three aspects of the paper are likely to strike the contemporary reader most forcibly. Initially it seems alien as it describes a world of collectivist industrial relations that was erased by the Conservative government elected in 1979. Yet on closer reading its main theme – reforming corporate accountability – emerges as all too familiar, as worker exploitation and other corporate scandals have continued largely unchecked to the present. And we may reflect that more recent research into policy transfer has improved our contemporary understanding of the barriers to corporate governance reform since the 1970s. Clegg correctly cautioned against attempting to import institutions from countries such as Germany into the UK, a view that has since been refined by analysis of the contrasts between co-ordinated and liberal market economies. Reforming corporate governance requires tailor-made policies, not those transferred merely on grounds of success in their original host countries.